Pembangunan instrumen penyelesaian masalah sains - Abdul Halim,; Lilia Halim,; T.Subahan bin Meerah,; Kamisah Osman, (penerbit ukm, 2010)
The aim of this research is to identify the science problem solving patterns espoused by students, teachers, and experts. The instrument used in this research consists of routine and non-routine problems as well as questionnaires of routine and non-routine problem solving. The steps of developing the g instrument involve development of routine and non-routine problems, development of questionnaire items of science problem solving, expert evaluation, and pilot test of the instrument to determine the validity and reliability of the instrument. The non-routine and routine problems were based on literature review and modification of questions from Sijil Pelajaran Malaysia examination for Physics, Chemistry and Mathematics. The development of questionnaire items refers to the definitions of construct based on the literature review. The analytical marking scheme of the routine and non-routine problem solving were developed based on the suggestions of expert. The content and face validity of the instrument was done by six experts. The result of the pilot test shows that the range of the Cronbach alpha is between 0.70 to 0.90. Where as the inter-item correlation coefficients are from 0.14 to 0.35. The development and validating steps of the instrument that can be applied to other field of science